Homeopathy and Weather Conditions - Schrijvers, Hanneke (Homœopathic Links, 2018)
Weather conditions can play an important role in causing suffering for those who are sensitive to it. Without addressing this with the indicated remedy, the suffering can change into a more severe disease condition.
Keywords: Cold and Damp; Dulcamara; Cystitis; Backache; Camping